Negative refraction in hyperbolic metamaterials - Mao, Tailai (Nanyang Technological University, 2021)
Electromagnetic metamaterials, which are artificial media formed by subwavelength structuring, are useful for manipulating light transmission and engineering electromagnetic space. These materials have a variety of peculiar properties that are seldom or never seen in nature. They can be used to implement useful functionalities in emerging light-based meta devices. In this project, we will discuss the use of the anisotropic bilayer graphene model which is one typical metamaterial to realize the negative refraction in Tera hertz region. This report also discusses the effects of isofrequency contour by using different surface graphene conductivity models. There are two main parts to this project, the first part will discuss the fundamental concepts of negative refraction in metamaterials, while the second part of this project will concentrate on the differences of results between using different surface graphene conductivity models.